Piano dei Servizi. Proposal for Contents and Guideline - Gerundo, Roberto; Graziuso, Gabriella (TeMA - Journal of Land Use, Mobility and Environment, 2014)
As an endless melting pot of experimentation and innovation, cities must reorganize and retrain compared to the growing new needs. In the light of the actual urban debate, it can be useful to do an in-depth study. In fact, the quality of urban life and collective well-being cannot be separated from the identification of a network of public services and facilities, that organizes and structures the city. That network is not resolved in the themes of pre-school and compulsory education, public interest, green spaces, car parks and public interest, but rather has a wider variety of types. Noting the failure of attempts to define, a priori, a quantity of universally valid services, it is necessary to rethink the ways and criteria of most of the infrastructural facilities. The "Piano dei Servizi" is the tool for the implementation of a concrete policy of services for public interest, and it means the transition between a planning standard, in terms of quantity, in a standard that meets quality requirements. It represents a specific section of the urban development plan, which has to consider problems and shortcomings, and try to solve them by finding opportunities which physical locations offer. In this way a planning standard is not configured as an abstract quantity, but as the material composition of the urban plan, which results in a land use and land development proposal.